Robot-Assisted Totally Intracorporeal Resection of Cutaneous Ureterostomy Tumor and Ileal Conduit Surgery: A Rare Case Report - Cai, Lingkai; Zhuang, Juntao; Cao, Qiang; Yuan, Baorui; Wu, Qikai; Li, Kai; Han, Jie; Yu, Hao; Lv, JianCheng; Feng, Dexiang; Liu, Peikun; Yu, Ruixi; et al. (Frontiers in Oncology, 2022)
Background: Radical cystectomy (RC) is the standard treatment for muscular invasive bladder cancer (MIBC) and some high-risk non-muscular invasive bladder cancer (NMIBC). Cutaneous ureterostomy is a common form of urinary diversion. However, after radical cystectomy, recurrence of upper urinary tract malignancies is possible. There is no relevant report on how to improve this situation's management. Case presentation: This case is a 56-year-old male patient hospitalized due to the development of a new tumor in the ureteral cutaneous stoma following radical cystectomy for more than five years. A biopsy of the tumor revealed high-grade urothelial carcinoma. Computed tomography (CT) revealed that the local soft tissue around the cutaneous stoma was thickened, but no other lesions were visible. After evaluating the case, we chose robot-assisted completely intracorporeal resection of cutaneous ureterostomy tumor and ileal conduit surgery. The total time for the operation and the blood loss were 400 minutes and 150 ml, respectively. Following surgery, the patient got standard chemotherapy in combination with immunotherapy. Additionally, ten months following the surgery, the patient did not experience disease progression or complications. Conclusion: The robot-assisted operation is safe and feasible for upper urinary tract tumor recurrence following radical cystectomy with cutaneous ureterostomy.